The Upside of Digital for the Middle East and North Africa : How Digital Technology Adoption Can Accelerate Growth and Create Jobs - Cusolito, Ana Paula (Washington, DC: World Bank, 2022)
The argument that digitalization fosters economic activity has been strengthened by the global COVID-19 pandemic. Because digital technologies are general-purpose technologies that are usable across a wide variety of economic activities, the gains from achieving universal coverage of digital services are likely to be large and shared throughout each economy. However, the Middle East and North Africa region suffers from a “digital paradox”: the region’s population uses social media more than expected for its level of gross domestic product (GDP) per capita but uses the internet or other digital tools to make payments less than expected.